Peran Kepala Madrasah Dalam Mengembangkan Budaya Religius di MTs. Negeri 2 Jepara - Munasir, Munasir; Mustofa, Muh Azam; Subaidi, Subaidi (Rumah Jurnal Institut Agama Islam An-Nawawi Purworejo, 2023)
The purpose of the study was to describe the role of the madrasah principal in developing a religious culture in madrasah, explain the factors that support and hinder in developing a religious culture, knowing the results of its development through the role of the madrasah principal. This type of research is descriptive qualitative. The location is at MTs. Negeri 2 Jepara. Data collection techniques are observation, interviews and documentation. The analysis is reduction, presentation, and conclusion drawing or verification. The results showed that; 1) The role of the madrasah head in developing a religious culture through 4 strategies: habituation, exemplary, value internalization, and partnership. 2). Supporting factors, including: a). strong leadership b). Highly committed teachers and staff, c). Curriculum integrated with religious values and religious activities d). An environment that supports religious practices e). Parental participation. Inhibiting factors, including: low commitment and understanding of teachers, students, and parents about the importance of religious culture; lack of resources/supporting facilities; demands of a dense curriculum; the influence of secular environment outside Madrasah; Non-involvement or lack of support from parents. 3) The development is in the form of: a). Dhuha prayers every day at break time, at 09.40 WIB in the mosque and accompanied by the teacher on duty; b.) Praying and tadarus al-Qurán; c). Jama'ah dhuhur prayer; d). Istighotsah / prayer together; e). PHBI.